Chemistry on Computers in East Africa – Lesson Plans from Collaborative Exchange - Rodenbough, Philip; Manyilizu, Majuto, Clement (My University, 2018)
Meeting the challenge of modern global chemistry education requires collaborations from many different actors. Here, we report the development of computer-based lessons on VSEPR and Unit Cells designed specifically for implementation in the unique environment of East African high schools. The lesson plans use software more commonly employed by materials science graduate students, here repurposed for the high school chemistry classroom. The lesson plans were successfully piloted in local schools, indicating their potential for wide impact. The complete lesson plans are provided for free here as in the supplemental information section. The careful design of the lessons based on specific environmental factors through multi-faceted contributors suggests a model of collaboration that could be useful in many other contexts.
Supplemental Materials: https://osf.io/hk82y/
Keywords: chemistry; computers; education; high school; science; stem; visualization